Selection pressure effects on the proportion and movement of resistance alleles introgressed from wheat in Aegilops cylindrica. (1st June 2016) - Martins, B A B; Leonard, J M; Sun, L; Zemetra, R S; Mallory‐Smith, C
Summary: In winter wheat in the USA, Aegilops cylindrica is one of the most troublesome weeds, while the pathogen Oculimacula spp. causes foot rot disease. Imazamox‐resistant (IR) and foot rot‐resistant (FR) wheat cultivars represent effective tools to control the weed and prevent disease infection. However, resistance allele (RA) movement between wheat and A. cylindrica facilitates the introgression process under herbicide and disease selection pressure. Field experiments using IR and FR A. cylindrica plants intermixed with susceptible plants were conducted to measure the proportion of the RAs in the progeny and RA movement with and without herbicide and disease selection. Yield components of A. cylindrica plants were determined across treatments. The herbicide RA proportion in the progeny was greater when plants were treated with the herbicide imazamox in both years. Disease RA proportion was greater with disease occurrence only in one year. Herbicide RA movement from resistant to susceptible plants was greater with herbicide than without it only in one year. Plants carrying the RAs had greater total spikelet weight and 1000‐spikelet weight compared with susceptible plants with or without selection. However, susceptible plants produced more spikelets than the resistant ones in the absence of selection. If plants within an A. cylindrica population acquire the herbicide RA, its proportion will increase each generation under selection. These findings contribute to the understanding of crop allele introgression into related species and the evolution of increased weediness, with weed management implications.